2006
DOI: 10.1088/0953-8984/18/24/002
|View full text |Cite
|
Sign up to set email alerts
|

Structure of expanded fluid Rb and Cs: a quantum molecular dynamics study

Abstract: We have performed quantum molecular dynamics simulations for expanded fluid Rb and Cs. We compare the pair correlation functions with results derived from neutron and x-ray scattering experiments. The experimentally observed structural changes with the density and temperature variation are reproduced. The density of states and the electronic charge density extracted from the simulations indicate a crossover from metallic to nonmetallic behaviour near the critical point due to a localization of electrons at nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…[27] . Such a feature has been predicted within chemical models earlier [28] and demonstrated recently for Rb [29,30] by QMD simulations in this region.…”
supporting
confidence: 71%
“…[27] . Such a feature has been predicted within chemical models earlier [28] and demonstrated recently for Rb [29,30] by QMD simulations in this region.…”
supporting
confidence: 71%
“…The availability of a reliable pseudopotential, which described structure and then dynamics quite well, prompted many classical MD simulation studies; see for example [42][43][44][45][46][47]. Later on first-principles methods have also been applied to simulate liquid rubidium [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity in this composition is ionic and decreases as it approaches the critical point. The structure of alkali metals in solid and liquid states was investigated by Kietzmann et al, Ross et al, and Gómez et al [17][18][19] Significant progress in understanding the processes of metallization of alkali metal vapours occurred after the appearance of a series of works by Likalter. [20,21] Likalter suggested that in the near-critical region, the conductivity's crucial role will not be played by thermally ionized (free) electrons but by bound electrons, whose classically available orbitals begin to overlap.…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity in this composition is ionic and decreases as it approaches the critical point. The structure of alkali metals in solid and liquid states was investigated by Kietzmann et al, Ross et al, and Gómez et al [ 17–19 ]…”
Section: Introductionmentioning
confidence: 99%